1984
DOI: 10.1111/j.1365-2125.1984.tb02388.x
|View full text |Cite
|
Sign up to set email alerts
|

Patients compliance in hypertension‐the importance of number of tablets.

Abstract: 1 The importance of number of tablets for patient compliance was investigated in 160 patients with mild-moderate essential hypertension treated with a ,8-adrenoceptor blocker and a thiazide diuretic. Mean BP at entry 146 + 16/92 + 8 mm Hg. 2 All patients were given pindolol 10 mg and clopamide 5 mg in one combination tablet or in separate tablets for 4 months respectively. Approximately 90% of the patients took > 90% of the prescribed dose throughout the study. 3 Mean BP decreased progressively and heart rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…Patient education by the physician is an important factor in helping to improve patient compliance and there is a wealth of data available to support this contention [15,[16][17][18][19][20][21][22]. Gatley [16] showed, as early as 1968, that once-daily dosing was to be preferred to multiple dosing whenever possible.…”
Section: Discussionmentioning
confidence: 99%
“…Patient education by the physician is an important factor in helping to improve patient compliance and there is a wealth of data available to support this contention [15,[16][17][18][19][20][21][22]. Gatley [16] showed, as early as 1968, that once-daily dosing was to be preferred to multiple dosing whenever possible.…”
Section: Discussionmentioning
confidence: 99%
“…Three cohort studies 9,25,26 (nϭ17 642) and 2 trials 18,20 (nϭ357) reported data on compliance among 17 999 hypertensive patients ( Figure 2). In the cohort studies, the use of an FDC was associated with a 21% increase in compliance with medications as compared with the use of the free-drug combination (OR: 1.21 [95% CI: 1.00 to 1.47]).…”
Section: Compliance and Persistence With Therapymentioning
confidence: 99%
“…A 24-h urine sample was collected, and volume, creatinine, and albumin were measured. We used the homeostasis model assessment to estimate insulin resistance (HOMA-IR) (24).…”
mentioning
confidence: 99%